Akibat Hukum bagi Kreditur Setelah Perjanjian Perkawinan Dibuat dan Telah Disahkan - Handoko, William Surya Putra (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2021)
This study aimed to analyze legal problems due to the change in the legal status of the debtor’s property in marriage which was previously a joint property into the personal property of each husband or wife.  This study used a statutory approach and an analysis approach, while the analysis techniques used grammatical interpretation and systematic interpretation. After the decision of the Constitutional Court was issued, the creation of marriage agreements that had been ratified would result in the law of separation of property and applied to third parties. The marriage agreement should not harm third parties.